What are the roles of antibodies versus a durable, high quality T-cell response in protective immunity against SARS-CoV2? (2020)
The first SARS-CoV2 vaccine(s) will likely be licensed based on neutralizing antibodies in Phase 2 trials, but there are significant concerns about using antibody response in coronavirus infections as a sole metric of protective immunity. Antibody response is often a poor marker of prior coronavirus infection, particularly in mild infections, and is shorter-lived than virus- reactive T-cells; strong antibody response correlates with more severe clinical disease while T- cell response is correlated with less severe disease; and antibody-dependent enhancement of pathology and clinical severity has been described. Indeed, it is unclear whether antibody production is protective or pathogenic in coronavirus infections. Early data with SARS-CoV2 support these findings. Data from coronavirus infections in animals and humans emphasize the generation of a high-quality T cell response in protective immunity. Yellow Fever and smallpox vaccines are excellent benchmarks for primary immune response to viral vaccination and induce long-lived virus-reactive CD8 T-cells, which are measurable within 1-4 months of vaccination. Progress in laboratory markers for SARS-CoV2 has been made with identification of epitopes on CD4 and CD8 T-cells in convalescent blood. These are much less dominated by spike protein than in previous coronavirus infections. Although most vaccine candidates are focusing on spike protein as antigen, natural infection by SARS-CoV-2 induces broad epitope coverage, cross-reactive with other betacoronviruses. It will be important to understand the relation between breadth, functionality and durability of T-cell responses and resulting protective immunity. It would be a public health and general trust-in-medicine nightmare - including a boost to anti-vaccine forces - if immune protection wears off or new disease patterns develop among the immunized. Data correlating clinical outcomes with laboratory markers of cell-mediated immunity, not only with antibody response, after SARS-CoV2 natural infection and vaccines may prove critically valuable if protective immunity fades or if new patterns of disease emerge.